The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1183/09031936.00122207
|View full text |Cite
|
Sign up to set email alerts
|

Early effective drainage in the treatment of loculated tuberculous pleurisy

Abstract: The role of early effective drainage in loculated tuberculous (TB) pleurisy treatment remains unclear.Consecutive patients with TB pleurisy subjected to anti-TB treatment and pigtail drainage (n564) were divided into three groups: 1) patients with free-flowing effusions irrigated with saline (free-flowing group; n520); 2) patients with loculated effusions irrigated with streptokinase (streptokinase group; n522); and 3) patients with loculated effusions irrigated with saline (saline group; n522). Pleural irriga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 18 publications
1
41
0
3
Order By: Relevance
“…Thirteen were then retrieved for full text review. Five [21][22][23][24][25] were then excluded because the study population consisted of mainly tuberculous pleural effusions, and one 26 was excluded because it did not have a control arm (ie, placebo) ( Fig 1 ). Thus, seven studies 7,[9][10][11][27][28][29] were included in the fi nal analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen were then retrieved for full text review. Five [21][22][23][24][25] were then excluded because the study population consisted of mainly tuberculous pleural effusions, and one 26 was excluded because it did not have a control arm (ie, placebo) ( Fig 1 ). Thus, seven studies 7,[9][10][11][27][28][29] were included in the fi nal analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Chung et al [22] demonstrated that pigtail catheter insertion may hasten resolution of tuberculous pleural effusion and reduce the occurrence of residual pleural thickening. On the contrary, Lai et al [23] found that pigtail catheter insertion for cases of tuberculous pleural effusion had no beneficial effects on residual pleural thickening development and did not shorten the duration of fever.…”
Section: Discussionmentioning
confidence: 99%
“…There are insufficient data to support evidence-based recommendations regarding the use of adjunctive corticosteroids in the treatment of tuberculous pleurisy (Engel et al 2007;Light 2010). The early removal of pleural fluid may also reduce the long-term impact of residual pleural fibrosis (Chung et al 2008;Light 2010). …”
Section: Tuberculous Pleurisymentioning
confidence: 99%